2016
DOI: 10.22267/rus.161802.35
|View full text |Cite
|
Sign up to set email alerts
|

Tipologías de estilos de vida en jóvenes universitarios

Abstract: Varela-Arévalo MT, Ochoa-Muñoz AF, Tovar-Cuevas JR. Tipologías de estilos de vida en jóvenes universitarios. Univ. Salud. 2016;18(2):246-256. DOI: http://dx.doi.org/10.22267/rus.161802.35 Resumen Introducción: La evidencia actual sobre la relación entre los estilos de vida y las principales problemáticas de salud mundial es amplia, dando cuenta del aumento en las cifras de comportamientos de riesgo y de sus impactos en la salud de la población. Objetivo: Identificar agrupaciones entre los jóvenes matricula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
0
11

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 16 publications
0
4
0
11
Order By: Relevance
“…However, insufficient levels of physical activity have been reported in several other studies. In 2016, 379 university students in Cali, Colombia, were analyzed 25 , showing groups of male and female students with unhealthy physical activity practices, regardless of whether they were working. Calestine et al (2017) 26 observed sedentary behavior and obesity in 512 students in the United States and related it to the excessive use of social media.…”
Section: Discussionmentioning
confidence: 99%
“…However, insufficient levels of physical activity have been reported in several other studies. In 2016, 379 university students in Cali, Colombia, were analyzed 25 , showing groups of male and female students with unhealthy physical activity practices, regardless of whether they were working. Calestine et al (2017) 26 observed sedentary behavior and obesity in 512 students in the United States and related it to the excessive use of social media.…”
Section: Discussionmentioning
confidence: 99%
“…Dado que los estudiantes pasan gran parte de su tiempo en la universidad, ésta se convierte en un espacio privilegiado en el que se pueden promover hábitos, entornos físicos y sociales que promuevan la salud y la calidad de vida de sus estudiantes (29) . Los resultados de este estudio pueden animar y orientar una reflexión sobre la mejora en los estilos de vida de los estudiantes y su desarrollo integral y, de esta forma, contribuir al mejoramiento de la escuela en términos de impacto positivo, mediados por los procesos curriculares, de planeación, de gestión educativa, y demás componentes del proceso formativo.…”
Section: Discussionunclassified
“…Regarding gender differences, several studies have supported that woman present lower levels of PA compared to men, both in college age and in adulthood (Blanco et al, 2017;Carriedo et al, 2019;Gómez et al, 2006;Wilson &Rodgers, 2002) (Castañeda-Vázquez, Campos-Mesa andDel Castillo-Andrés, 2016). In addition, recent studies identify the prevalence of sedentary lifestyles in university students, especially in women (García Puello & Herazo Beltrán, 2015;Arévalo, Muñoz & Cuevas, 2016, Puerta Mateus et al, 2019 In the study conducted by Arévalo, Muñoz & Cuevas (2016), after corroborating the greater sedentary lifestyle in women than in men, an attempt was made to provide an explanation for these differences. In addition to the arguments about inequalities in gender roles widely discussed by other studies, these differences could also be explained by less availability for physical activity reported by women, due to the multiplicity of activities they have to perform since their youth, as well as the important differences in the motivations they show for physical activity.…”
Section: Introductionmentioning
confidence: 99%